The role of maximal inspiratory pressure on functional performance in adults with heart failure - Rohan V. Shah; Lawrence P. Cahalin; Jacob M. Haus; Kelly Allsup; Amanda Delligatti; Cody Wolf; Erica R. Checko (Scioli); Jayashri R. Aragam; Daniel J. Gottlieb; Thomas D. Byard; Daniel E. Forman (ESC Heart Failure)
Abstract Background Exercise intolerance is common among adults with heart failure (HF) and is a strong prognostic indicator. We examined maximal inspiratory pressure (MIP) as an indicator of maximal and submaximal exercise capacity in older HF patients. Methods Fifty‐one patients age ≥ 50 years with HF underwent MIP testing via the PrO2 device. Peak oxygen uptake (VO2), 6 min walk distance (6MWD), 30 s sit‐to‐stand test (STS), gait speed (GS), grip strength and lower extremity muscle strength [one‐repetition maximum (1RM)] were measured. Correlation and exploratory multiple regression analyses investigated relationships between MIP, left ventricular ejection fraction (LVEF), age, body mass index (BMI) and physical function. MIP was then stratified by median (64 cm H2O), and endpoints were compared between median groups. Results The median age was 69 years [interquartile range (IQR): 66–73], and the median LVEF was 36.5% (IQR: 30%–45%). Regression identified MIP as an independent predictor for grip strength, 6MWD, 1RM weight and 30 s STS after adjustment for age, BMI and LVEF. MIP greater than the median (n = 25) independently predicted and reflected greater peak VO2 [14.2 (12.8–18.1) vs. 11.5 (9.7–13.0) mL/kg/min; P = 0.0007] as well as 6MWD, 1RM, 30 s STS and GS (all P < 0.05). Conclusion The analysis demonstrates that MIP is a novel biometric for exercise tolerance in adults with HF. Assessments of MIP are safe and convenient, with the potential to enhance routine HF surveillance and provide novel biometrics to guide HF therapeutics.